Impact of Social Classes on Academic Performance of Pupils in Public Primary Schools in Kabale District. - Ampeire, Justus (Kabale University, 2025)
This study, titled "The Impact of Social Classes on Academic Performance of Pupils in Public Primary Schools in Kabale District," was conducted within Kabale Municipality. The research had three specific objectives: to examine the different social classes present in society that influence the academic performance of pupils at Kikungiri Primary School, to investigate the role of the school, home, and environment in fostering social classes, and to assess the impact of social classes on pupils' academic performance at Kikungiri Primary School in Kabale Municipality. A descriptive cross-sectional survey design was used to collect data on the impact of social classes on academic performance. The study employed both quantitative and qualitative methods for data collection and analysis. Quantitative data was analyzed using statistics and numerical tools to ensure objectivity, while qualitative data generated concepts and strategies. The findings revealed that age (36.6%) was one of the primary social classes affecting pupils’ academic performance, with age sets influencing the allocation of rewards and status, which, in turn, impacted educational outcomes. Gender, cited by 24.4% of respondents, was also identified as a key factor, with participants noting that gender is socially constructed rather than biologically determined. Additionally, 36.6% of respondents highlighted the source of basic needs as a significant influence, while other factors included maximization of profits (30.5%), improved learning activities (14%), good quality education (9.8%), and other aspects (8.5%). The study emphasized that social stratification is an inherent part of every society, but measures can be taken to minimize its impact on education. Recommendations include providing equitable education opportunities for all pupils in Kabale District. The study specifically suggested ending the categorization of schools into Extra-County, County, and District levels and implementing a uniform admission policy to create a more inclusive education system.